واقع وآفاق الجباية المحلية في الجزائر - عباس إبراهيم, علي; حسيني, منال; خليفة, أحمد (جامعة الوادي - University of Eloued, 2018)
استهدفت الدراسة تشخيص وتحليل واقع الجباية المحلية في الجزائر، والبحث في إمكانية تطويرها والارتقاء بها إلى مستوى ذو فاعلية أفضل، لتتوصل إلى أن الجباية المحلية تمثل المحرك القاعدي للتنمية الاقتصادية والاجتماعية على مستوى الجماعات الإقليمية، فهي تشكل الحصة الأكبر من مجموع مواردها المالية، غير أن هذه الأخيرة تواجه عدة تحديات وصعوبات في تعبئة تلك الموارد الجبائية، مما يعيق تأدية مهامها بصفة متوازنة ومتكاملة، وهو الشيء الذي أدى إلى إدخال إصلاحات دورية عليها والبحث الدائم والمستمر في كيفية تطويرها لغرض تعزيز مالية الجماعات الإقليمية بالشكل الذي ينعكس على مستوى فاعليتها وكفاءتها The study aimed at diagnosing and analyzing the reality of local tax collection in Algeria and exploring the possibility of developing it and upgrading it to a more effective level. It concludes that local collection is the basic engine of economic and social development at the regional level. It is the largest share of total financial resources. The latter faces several challenges and difficulties in mobilizing these tax resources, which hinders the performance of their tasks in a balanced and integrated manner, which led to the introduction of periodic reforms and constant and continuous research on how to develop them for the purpose of strengthening the finances of regional groups in the form of Reflected in their effectiveness and efficiency.
The reality and prospects of local collection in Algeria
مقال
Keywords: السلطة المركزية، الجماعات المحلية-الإقليمية، الجباية المحلية، الضرائب،; Central Authority, Local-regional groups, Local collection, Taxes